Acute phase proteins levels in horses, after a single carbohydrate overload, associated with cecal alkalinization - Peixoto Rabelo, Isabela; Barroco de Paula, Vanessa; Carvalho Bustamante, Caio; Santana, André Marcos; Gomes da Silva, Daniela; Baldassi, Amanda Cristina; Canola, Paulo Aléscio; Araújo Valadão, Carlos Augusto (Frontiers in Veterinary Science, 2023)
Horses submitted to carbohydrate overload can develop laminitis due to changes in cecal pH and microbiota, followed by an increase in transmural absorption of luminal content, including bacterial toxins. In response to acute injury there is hepatic overproduction of several proteins known as acute phase proteins (APP). Few studies have evaluated protein fractionation to characterize the inflammatory response in acute laminitis. The aim of this study was to test the viability of an experimental model to induce acute laminitis, using a single carbohydrate overload, and the influence of a buffering solution on the development of the disease; also, study the kinetics of APP during acute laminitis, as well as the correlation between these proteins and clinical signs associated to this syndrome. Ten healthy horses were divided in a factorial and randomized way into four groups (n = 5): control group (CG), starch group (SG), buffer group (BG), starch + buffer group (SBG). They were evaluated at seven times (T0h, T4h, T8h, T12h, T24h, T48h, T72h), which included clinical evaluation and blood sample collection. Total serum protein and albumin concentrations were determined by colorimetry and the other APP by polyacrylamide gel electrophoresis containing sodium dodecyl sulphate and commercial ELISA kits. Data were analyzed by two-way ANOVA, followed by Tukey’s test (p < 0.05). The correlation between clinical signs and APP were verified using the Pearson’s correlation coefficient. 40% of the animals from SG and 60% from SBG developed clinical laminitis. A single administration of buffer solution was not able to prevent clinical signs of laminitis. There was no difference between groups on total serum protein, albumin, serum amyloid A and C-reactive protein concentrations (p > 0.05). Transferrin, considered a negative APP, showed a positive response pattern in SG and SBG. Ceruloplasmin had a positive correlation with Obel grade, heart rate on animals from SGB and number of steps on horses submitted to starch overload (SG and SBG). Ceruloplasmin, α-1-antitrypsin and haptoglobin concentrations increased in SBG, suggesting an inflammatory response in animals of this group. Changes in clinical parameters were also more evident in the SBG, corroborating the protein fractionation findings.